MAPPING THE DRIVERS OF TAX COMPLIANCE TO ESTABLISH STRATEGIC IMPROVEMENT PRIORITIES THROUGH IMPORTANCE–PERFORMANCE - Musyaffi, Ayatulloh Michael; Khairunnisa, Hera; Wastuti, Wahyu; Purwohedi, Unggul; Yusuf, Muhammad; Sudiati, Rochma; Wolor, Christian Wiradendi; Adha, Maulana Amirul (JRAK, 2026)
Tax compliance plays a pivotal role in strengthening regional fiscal capacity. This study aims to map the determinants of tax compliance by analyzing taxpayers’ perceptions of awareness, service quality, public policy evaluation, and monitoring mechanisms, employing a descriptive quantitative approach. A total of 354 valid responses were obtained through accidental sampling in public activity centers. Data were analyzed using Importance–Performance Map Analysis (IPMA) to identify strategic priorities. The findings show taxpayers’ awareness and compliance demonstrate the highest performance, while service quality, policy evaluation, and monitoring remain at a moderate level. This study provides evidence-based insights to support the enhancement of regional tax administration and the formulation of more effective tax policy reforms.